ChemInform Abstract: A New Family of Nucleophiles for Photoinduced, Copper‐Catalyzed Cross‐Couplings via Single‐Electron Transfer: Reactions of Thiols with Aryl Halides under Mild Conditions (O °C). Issue 49 (3rd December 2013) - Uyeda, Christopher; Tan, Yichen; Fu, Gregory C.; Peters, Jonas C.
Abstract A versatile photoinduced, copper‐catalyzed method for coupling aryl thiols with aryl halides is reported.